Sex and side determination of human hip bone by metric parameters of its posterior border - Sarita R Margam; Megha A Doshi; Surekha D Jadhav; Raosaheb J Patil; Manoj P Ambali (Wolters Kluwer Medknow Publications, 2013)
Background: Identification of sex from skeletal remains is of medico-legal and anthropological importance for forensic experts, anthropologists and anatomists. Hip bone is considered as an ideal bone for sex determination as it provides the highest accuracy levels for sex determination. Aims: To determine the sex and side of the human hip bones by using different metric parameters of posterior border of hip bone. Material and methods: In present study, 200 (100 males and 100 females) dried adult human hip bones of known sex were collected. Two parameters were studied and statistically analysed by paired and unpaired 't'test. Results: In males, distance from the posterior superior iliac spine to the superior border of ischial tuberosity was the discriminant criteria to sex the hip bones while in females, it was distance between the posterior inferior iliac spine (PES) to ischial tuberosity (IT). Statistically significant difference between the mean related to side were seen in both the variables. Conclusion: These two parameters can be used for sexual dimorphism as well as side determination of human hip bones or its fragments.